No-fault compensation following adverse events attributed to vaccination: a review of international programmes - Clare Looker; Heath Kelly (The World Health Organization, 2011)
Programmes that provide no-fault compensation for an adverse event following vaccination have been implemented in 19 countries worldwide,the first in Germany in 1961 and themost recent in Hungary in 2005.We performed a review of these programmes and determined elements that were common to all of them: administration and funding, eligibility, process and decision-making, standard of proof, elements of compensation and litigation rights. Most programmes were administered by state or national governments except in Finland and Sweden where they are coordinated by pharmaceutical manufacturers.Although funding is usually from Treasury,Taiwan (China) and the United States of America impose a tax on vaccine doses distributed. Decisions on compensation are made using established criteria or assessed on a case-by-case basis, while the standard of proof required is usually less than that required for court cases. Benefits provided by programmes include medical costs, disability pensions and benefits for noneconomic loss and death. Most countries allow claimants to seek legal damages through the courts or a compensation scheme payout but not both. We conclude that a variety of programmes, based on ethical principles, have been successful and financially viable in developed countries throughout the world. We believe there is a strong argument for widespread implementation of these programmes in other developed countries.